The alpheid shrimp genus Leslibetaeus Anker, Poddoubtchenko & Wehrtmann, 2006 in the Western Atlantic, with description of a new species from Tobago (Crustacea, Decapoda) - Anker, Arthur (Zootaxa, 2011)
A miniature alpheid shrimp, Leslibetaeus caribbaeus n. sp., is described on the basis of a single female specimen collected in Sandy Bay, Tobago, in 1992. The new species is closely related to L. coibita Anker, Poddoubtchenko & Wehrtmann, 2006 from the Pacific coast of Panama, the type species and the only other known species of Leslibetaeus Anker, Poddoubtchenko & Wehrtmann, 2006, differing from it in several morphological characters. With the discovery of L. caribbaeus n. sp., Leslibetaeus becomes a genus with transisthmian (= amphi-American) distribution. In addition, L. coibita is reported for the first time since original description and its range is extended by 400 km southwards. The generic diagnosis of Leslibetaeus is slightly emended.